Effects of feeding excess dietary crude protein from soybean meal and dried distillers grains with solubles on nursery pig performance - Williams, S.M.; Paulk, C.B.; Issa, S.; Gugle, Terry L.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to determine the effects of feeding excess dietary CP to nursery pigs. In Exp. 1, a total of 105 nursery pigs (PIC TR4 × 1050, initially 22.9 lb and 35 d of age) were used in a 21-d growth assay to determine the effects of feeding excess CP from soybean meal to nursery pigs. The pigs were fed a pelleted commercial starter diet for the first 14 d after weaning, and the experimental treatments were fed for the next 21 d. Treatments consisted of 3 corn-soybean meal-based diets formulated to different CP levels: (1) 22.5%, (2) 25%, and (3) 27.5% CP. Increasing CP from 22.5 to 27.5% had no effect (P > 0.19) on ADG, ADFI, or F/G. In Exp. 2, a total of 105 nursery pigs (PIC TR4 × 1050, initially 22.1 lb and 35 d of age) were used in a 21-d growth assay to determine the effects of excess CP from dried distillers grains with solubles (DDGS) on nursery pig growth. The pigs were fed a pelleted commercial starter diet for the first 14 d after weaning and the experimental treatments for the next 21 d. Treatments were corn-soybean meal-based diets formulated to 22.9 and 25% CP and a diet with 30% DDGS formulated to 25% CP. Increasing the CP concentration had no effect (P > 0.12) on ADG, ADFI, or F/G. However, pigs fed the DDGS had poorer (P < 0.04) F/G compared to pigs fed the corn-soybean meal-based diet formulated to 25% CP. Our data suggest that nursery pigs can tolerate CP levels up to 27.5% without negative effects on growth performance. Additionally, the inclusion of 30% DDGS in nursery pig diets did not have a significant impact on ADG or ADFI, but did negatively affect F/G.
Keywords: Swine; Dried distillers grains with solubles; Excess crude protein; Soybean meal